Peningkatan Kesehatan Dan Kebugaran Jasmani Masyarakat Desa Bontomatene Kecamatan Marusu Melalui Kegiatan Olahraga - Aminuddin; Muh. Khaedar (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Health and Physical Fitness are very important in physical activity work, good body condition will support daily activities to the maximum. Likewise, this also applies to village communities, especially in Bontomatene' village, Marusu District, Maros Regency. The people of Bontomatene village, who depend on farming and as fishermen, really need to maintain fitness and physical health. Excellent physical condition gives the body the ability to carry out activities well without significant fatigue. The method used in this PkM is outreach to the community. Through this activity, the village community understands the importance of health and physical fitness to improve the quality of life, especially in terms of physical health, because in essence exercise can be done anytime and anywhere according to the right dosage. This activity had a very positive impact on the Bontomatene village community, who previously did not understand why they should exercise, finally started to improve their health and fitness. The village community also understood how to prevent disease by doing physical exercises as a series of sports for health.